Instantaneous GPS-Galileo attitude determination: single-frequency performance - Nadarajah, Nandakumaran; Teunissen, Peter; Raziq, N. (IEEE, 2013)
New and modernized global navigation satellite systems (GNSSs) are paving the way for an increasing number of applications in positioning, navigation, and timing (PNT). A combined GNSS constellation will significantly increase the number of visible satellites and, thus, will improve the geometry of observed satellites, enabling improvements in navigation solution availability, reliability, and accuracy. In this paper, a global positioning system (GPS) +Galileo robustness analysis is carried out for instantaneous single-frequency GNSS attitude determination. Precise attitude determination using multiple GNSS antennas mounted on a platform relies on successful resolution of the integer carrier-phase ambiguities. The multivariate-constrained least squares ambiguity decorrelation adjustment (MC-LAMBDA) method has been developed to resolve the integer ambiguities of the nonlinearly constrained GNSS attitude model that incorporates the known antenna geometry. In this paper, the method is used to analyze the attitude determination performance of a combined GPS +Galileo system. Special attention is thereby given to the GPS and Galileo intersystem biases (ISBs).The attitude determination performance is evaluated using GPS/Galileo data sets from a hardware-in-the-loop experiment and two real-data campaigns. In the hardware-in-the-loop experiment, a full GPS/Galileo constellation is simulated, and performance analyses are carried out under various satellite-deprived environments, such as urban canyons, open pits, and other satellite outages. In the first real-data experiment, single-frequency GPS data, combined with the data of Galileo in-orbit validation element (GIOVE) satellites GIOVE-A/GIOVE-B (the two experimental Galileo satellites), are used to analyze the two constellation attitude solutions. In the second real-data experiment, we present the results based on single-frequency data from one of the Galileo IOV satellites, combined with the data of GIOVE-A and GPS. We d- monstrate and quantify the improved availability, reliability, and accuracy of attitude determination using the combined constellation.